Small intestinal bacterial overgrowth - small intestine, big struggle - Aleksandra Dembowska; Maciej Dubaj; Karol Bigosiński (Journal of Education, Health and Sport, 2022)
The gut microbiota plays an important role in the proper functioning of the human body. The microbes present in the intestines are important for the correct functioning of the digestive tract as well as other, often distant, organs of the human body. Unfavorable conditions may lead to an imbalance of intestinal microorganisms, leading to unfavorable consequences.